Influence of playing a prolonged tennis match on shoulder internal range of motion - Martin, C.; Kulpa, R.; Ezanno, F.; Delamarche, P.; Bideau, B. (The American Journal of Sports Medicine, 2016)
Background: Shoulder range of motion (ROM) deficits have been identified as an injury risk factor among tennis players. It is well known that shoulder internal rotation deficit increases with age and years of play, but there is a lack of knowledge regarding the influence of a prolonged tennis match on shoulder ROM. Purpose: To examine changes in shoulder ROM during a prolonged tennis match. Study Design: Descriptive laboratory study. Methods: Shoulder passive internal and external rotation ROM were measured on 8 male tennis players before, every 30 minutes during, and just after a 3-hour tennis match. Total ROM was calculated as the combination of shoulder internal and external rotations. Ball velocity on the serve was measured with a radar gun before, at midmatch, and just after the match. Results: Decreases in shoulder internal rotation (-20.8°; P = .005), total ROM (-24.6°; P = .001), and serve velocity (-1.8 m/s; P = .002) were observed at the end of the match. No statistically significant difference was observed for shoulder external rotation after the match (P = .460). Conclusion: Passive shoulder internal rotation and total ROM are significantly decreased during a 3-hour tennis match. Clinical Relevance: The results show that a prolonged tennis match play can modify values of shoulder ROM.